Coproprevalence of canine infestation by Echinococcus granulosus in an endemic hidatidosis disctrict in Peru - Montalvo, Raúl (2018)
The objective of this study was to determine the coproprevalence of Equinococcus granulosus in dogs of the rural district of San José de Quero, located in the province of Concepción, Junín region, central Peru. The cross-sectional study was carried out in 2015 in all three annexes of the district. Faecal samples were collected from 152 dogs from the same number of randomly selected households and processed using the Echinococcus granulosus-specific ELISA technique. The 50% of samples (Usibamba 61.0%, Chaquicocha 51.0% and San José de Quero 41.9%) were positive to the parasite. Likewise, it was determined that the average number of dogs per house was 2.3, 40.9% of the owners feed the dogs with fresh viscera of slaughtered cattle, the proportion of dogs that defecate outside the house was 91.3%, and that 18.4% reported having had a family member with a hydatid cyst. It is concluded that canine infestation by E. granulosus is frequent in the district San José de Quero, which is facilitated by the habits of the owners and the epidemiological behaviours of dogs.